Analisis Keterampilan Berpikir Kritis Peserta Didik Kelas VII SMP Negeri di Kecamatan Pattallassang Kabupaten Takalar - Ayu Nur Indah Sari; Hasanuddin Hasanuddin; Ramlawati Ramlawati (Celebes Science Education, 2024)
This research aims to determine: (1) The level of critical thinking skills of class VII students at State Middle Schools in Pattallassang District, Takalar Regency, and (2) Description of the critical thinking skills of class VII students at State Middle Schools in Pattallassang District, Takalar Regency. The research method used is quantitative descriptive. The population of this study were students in class VII of SMPN in Pattallassang District, Takalar Regency, namely SMPN 1 Takalar and SMPN 2 Takalar. The sampling technique used was random sampling technique so that from a population of 587 a sample of 250 students was obtained. The research instrument used was a test of 20 questions in multiple choice form. Based on the results of data analysis, it is known that: (1) the level of critical thinking skills of class VII students at State Middle Schools in Pattallassang District, Takalar Regency is 56.5, which is in the sufficient category; (2) The critical thinking skills of students in class VII of State Middle Schools in Pattallassang District, Takalar Regency when giving a simple explanation are in the sufficient category with a percent value of 51%, the indicator for building basic skills is in the sufficient category with a percent value of 55.6%, concluded is in the sufficient category with a percent value of 50.8%, providing further explanation is in the sufficient category at 57.1% and the indicator for managing strategies and tactics is in the high category with a percent value of 66.7%. Students' critical thinking skills need to be improved and trained again, creative and innovative learning methods will influence students' enthusiasm for learning and also influence students' critical thinking skills.